(untitled) (Advances in Applied Mathematics and Mechanics, 2013)
Taking vibration converter of intelligent damper for drill strings as the study object, this paper analyzes the influential factors of motion state of the ball and conducts an explicit dynamics simulation by establishing a mechanics model of vibration converter. The study basis is Newton's laws of motion, D'Alembert's principle and Hertz contact theory. And we use world coordinate system, rotating coordinate system and Frenet coordinate system to deduce kinematics equations of vibration converter. The ultimate result demonstrates that the axial velocity and maximum contact stress change with the increment of ball diameter and helix angle. It also proves the validity of our derived kinematics and mechanical models and provides a good consultant value for the design and theoretical arithmetic of vibration converter for intelligent damper of drill strings.